FAKTOR YANG MEMENGARUHI KINERJA PERAWAT DI RSUD PROF. DR. H. ANWAR MAKKATUTU KABUPATEN BANTAENG - Salim, Andi Azizah Nur Fadhilah; Andi Muhammad Multazam; Andi Nurlinda; Sumiaty; Yuliati; Reza Aril Ahri (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2026)
Nurse performance is an important indicator in determining the quality of nursing services and overall hospital performance. Nurse performance is influenced by various psychosocial and individual factors, including work motivation, work stress, job satisfaction, and nutritional status. This study aimed to analyze the factors affecting nurse performance with job satisfaction as an intervening variable at RSUD Prof. Dr. H. Anwar Makkatutu, Bantaeng Regency. The findings of this study are expected to provide input for hospital management in improving nurse performance and the quality of nursing services. This study employed a cross-sectional design with a quantitative approach. The study sample consisted of all nurses working at RSUD Prof. Dr. H. Anwar Makkatutu, selected using a simple random sampling technique. The research variables included work motivation, work stress, nutritional status, job satisfaction, and nurse performance. Data were analyzed using univariate analysis, bivariate analysis with pearson correlation, and multivariate analysis using path analysis. The results showed that job satisfaction had a direct and significant effect on nurse performance. Work motivation had a positive and significant effect on job satisfaction, while work stress had a negative and significant effect on job satisfaction. Job satisfaction was proven to mediate the effects of work motivation and work stress on nurse performance. Nutritional status had no significant effect on job satisfaction or nurse performance. It is recommended that hospital management prioritize strategies to improve job satisfaction and work motivation, as well as effective management of work stress, in order to enhance nurse performance and the quality of nursing services.